The Correlation of Community Development (CD) Program and Image of Company PT. Perkebunan Nusantara V (PTPN-V) Recipients Help Education Sector at Pekanbaru - Anuar Rasyid; Fuad Muchlis (Jurnal Komunikasi Pembangunan, 2014)
AbstractStudy aimed to (1) analyze the relationship between the Community Development (CD) program and image of  PTPN V in the education sector beneficiaries in Pekanbaru;  (2) analyze the factors inhibiting and supporting the Community Development (CD) of PTPN-V. The first study  conducted  using quantitative methods  while  the second study  using qualitative methods. Results showed a strong correlation between Community Development (CD) program  and image  of  PTPN V in the education sector beneficiaries in Pekanbaru. Furthermore,  the  factors inhibiting the Community Development (CD) program that funds the education sector is relatively limited and should be selected for the program beneficiaries.  The factor supporting the education sector  of  Community Development (CD) program  was  a  good cooperation between company and educational organizations beneficiary  of  education program of Community Development (CD).Keywords:  community development, image of company